2017
DOI: 10.1007/978-3-319-47403-8
|View full text |Cite
|
Sign up to set email alerts
|

SiGe-based Re-engineering of Electronic Warfare Subsystems

Abstract: of the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As a third-generation wide band gap semiconductor, silicon carbide (SiC) has emerged abundant interests because of its excellent chemical inertness and good capability with existing silicon-based electro devices. [15][16][17] Besides, SiC has been proven as a qualied candidate for the application in extreme condition, 18,19 and its high charge transport rate makes it possible to fabricate gas sensors with short response/recovery time. 20 Soo et al demonstrated that SiC material is the best candidate for some particular situations (chemical synthesis, vapor-turbine tests, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…As a third-generation wide band gap semiconductor, silicon carbide (SiC) has emerged abundant interests because of its excellent chemical inertness and good capability with existing silicon-based electro devices. [15][16][17] Besides, SiC has been proven as a qualied candidate for the application in extreme condition, 18,19 and its high charge transport rate makes it possible to fabricate gas sensors with short response/recovery time. 20 Soo et al demonstrated that SiC material is the best candidate for some particular situations (chemical synthesis, vapor-turbine tests, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC), as one of the most representative wide band gap semiconductors (2.39 eV for 3C‐SiC), has raised substantial attention because of its superior properties, including high mechanical strength, chemical inertness, and good thermal stability . Because of these unique features, SiC possesses the potential for applying in harsh environment (corrosion environment, oxidizing atmosphere, high‐temperature, etc) . Particularly, SiC also has the ability to transfer charge carriers rapidly owing to its high electron mobility .…”
Section: Introductionmentioning
confidence: 99%